Implementation of Inclusive Education in Elementary Schools: Challenges and Opportunities in Learning - Nur Wulandani; Ayi Abdurahman; Rini Lestari; Anjar Mahmudin NST; Awayundu Said (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2025)
Inclusive education is an approach that aims to provide equal educational rights for all students, including those with special needs. This research aims to identify the challenges faced in the implementation of inclusive education in primary schools as well as opportunities that can be used to overcome them. This study uses qualitative methods with interviews, observations, and documentation approaches to obtain in-depth data on inclusive education practices in several elementary schools in Indonesia. The study results show that the main challenges faced include the lack of inclusive teacher training, limited support facilities for students with special needs, and the lack of effective social interaction in the school environment. However, some opportunities can be utilized, such as providing practice-based continuous training, improving disability-friendly facilities and infrastructure, establishing social support groups in schools, and using educational technology as an interactive learning tool. The conclusion of this study confirms that a practical training-based approach for teachers, investment in inclusive facilities, the development of social activities that support the interaction of students with special needs, and the use of digital media can increase the effectiveness of implementing inclusive education. The main contribution of this research is to provide new insights into practical strategies for addressing the challenges of inclusive education at the primary school level, which can be a reference for policymakers and education practitioners.